Proceedings of the Tenth ACM/IEEE Symposium on Architectures for Networking and Communications Systems 2014
DOI: 10.1145/2658260.2658272
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and programmable ethernet switching with a NoC-enhanced FPGA

Abstract: Communications systems make heavy use of FPGAs; their programmability allows system designers to keep up with emerging protocols and their high-speed transceivers enable high bandwidth designs. While FPGAs are extensively used for packet parsing, inspection and classification, they have seen less use as the switch fabric between network ports. However, recent work has proposed embedding a networkon-chip (NoC) as a new "hard" resource on FPGAs and we show that by properly leveraging such a NoC one can create a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…In 2010, the MDN packet switch was proposed as an extension to UDN [13], [24]. In [25], Bitar et al discussed a possible implementation of a crossbar fabric using NoCenhanced FPGA and evaluated its performance for various routing algorithms. In [26], Karadeniz et al suggested one stage switch with Networks-on-Chip fabric.…”
Section: B Network-on-chip For Packet Switching Fabricsmentioning
confidence: 99%
“…In 2010, the MDN packet switch was proposed as an extension to UDN [13], [24]. In [25], Bitar et al discussed a possible implementation of a crossbar fabric using NoCenhanced FPGA and evaluated its performance for various routing algorithms. In [26], Karadeniz et al suggested one stage switch with Networks-on-Chip fabric.…”
Section: B Network-on-chip For Packet Switching Fabricsmentioning
confidence: 99%
“…In 2010, the Multidirectional NoC (MDN) packet-switch was proposed as an extension to UDN [9]. More recent results [10] discussed a possible implementation of a crossbar fabric using NoCenhanced FPGA, and evaluated its performance for various routing algorithms. In [8], Karadeniz et al suggested one stage packet switch with NoC fabric.…”
Section: Related Workmentioning
confidence: 99%
“…In 2010, the Multidirectional NoC (MDN) packet switch was proposed as an extension to UDN [11]. More recent results [12] discussed a possible implementation of a single-stage crossbar fabric using NoC-enhanced FPGA and evaluated its performance for various routing algorithms. In [10], Karadeniz et al suggested a single-stage switch with Networks-on-Chip fabric.…”
Section: Related Workmentioning
confidence: 99%